Stop-bang score and mandibulohyoid distance in prediction of difficult airway in patients who come for elective surgery requiring endotracheal intubation in Hospital USM - Lee, Kok Tong (2017)

(untitled)
Incidence of difficult laryngoscopy and difficult intubation are higher among patients with obstructive sleep apnoea (OSA). Precision in making the diagnosis and predicting difficult laryngoscopy preoperatively may help to reduce anaesthetic complications. This study was designed to evaluate the diagnostic performance of combined and non-combined radiological parameter (mandibulohyoid distance) and STOP-BANG questionnaire as screening tool.Total of Forty-one subjects who score >3 using STOP-BANG questionnaire screening were recruited during admission (STOP BANG score >3 indicate the subject at risk for OSA). Lateral cephalometry( lateral head and neck x ray) was done to measure for mandibulohyoid distance and other radiological parameters. Evaluation for difficult laryngoscopy was carried out during general anaesthesia. Cormarch Lehance view of grade 3 and 4 were considered as difficult intubation, grade 1 and grade 2 were considering not difficult intubation. Result analysed using multiple logistic regression to look for association between STOP-BANG score and mandibulohyoid distance with difficult intubation in OSA patients.STOP-BANG score, mandibulohyoid distance (mm) , were higher in the OSA group. OSA patients had a higher incidence of difficult laryngoscopy and intubation. There was association between STOP-BANG score and mandibulohyoid distance with difficult intubation in OSA patients. AUC (95% CI) ,0.86 (0.74,0.97). In prediction of airway difficulty, for STOP BANG alone, sensitivity and specificity ( 85.71% ,66.7% respectively), for mandibulohyoid alone , sensitivity and specificity(77.8%, 69.6% respectively). Combination of STOP-BANG score and mandibulohyoid distance had improved the specificity and sensitivity of the screening tool to predict difficult airway.(77.3% and 84.2% respectively).The STOP-BANG score and mandibulohyoid distance proved to be useful in the preoperative diagnosis of difficult laryngoscopy and intubation. The performance of the diagnostic tool improved when combined both STOP-BANG score and mandibulohyoid distance (mm) .OSA patients were more prone to difficult laryngoscopy.